Probing Biomolecular Machines with Graphics Processors. - PHILLIPS, JAMES C.; STONE, JOHN E. (Communications of the ACM, 2009)
The article presents a discussion of the use of computer graphics processing units (GPUs) to model molecular biological phenomena. It is noted that the increasing availability of inexpensive GPUs has led to the development of parallel computer techniques, and allowed increasingly complex simulations to be run on desktop machines. The usefulness of creating interactive visual representations of mathematical models of biological systems is emphasized. Examples are provided of research areas, such as protein folding, which can be better investigated using such methods, and a discussion of the aspects of computer science which are particularly applicable to this field is included.